Virtuality of Online Religion in Cyberspace: Study of Virtual Hajj in Metaverse Discourse - Fadillah, Nur Aisyah; Murad, Ahmad Nailul (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
The article examines the phenomenon of shifting religion in Cyberspace, where the practices from the offline to the online sphere are indicated by the COVID-19 pandemic, which has changed the social structure and behaviour of Indonesian society. For the most part, hajj metaverse discourse tends to use this new public space to be a clear visual manifestation of religious identity. Using this theoretical framework of Champbell and Sheldon, religion needs to adjust to all threats and risks in Cyberspace. The article questions to what extent the metaverse Hajj discourse has shifted religious authority in Cyberspace. How has the pandemic impacted the discourse of Hajj through the metaverse? as seen from the debate of restrictions on places of worship and leading to alternative ways to enjoy the Hajj pilgrimage during the COVID-19 pandemic? Using qualitative methods and ethnographic study, discourse on metaverse hajj makes it impossible to shift religious authority because, in historical, legal, and procedural terms, it is problematic to apply in Muslim society. On the other hand, the ritual of Hajj cannot be broken because a series of activities requires physical presence. The second finding is that the law of Hajj in the metaverse to spread COVID-19 does not validate the Hajj itself because it does not fulfil the pillars of Hajj. Findings reveal that while the metaverse offers potential benefits such as increased accessibility and immersive experiences, it also raises concerns regarding fulfilling Hajj's core tenets, which require physical presence and adherence to specific rituals. The study concludes that although virtual Hajj may serve as a supplementary tool for education and familiarization, it cannot replace the actual pilgrimage due to its inherent limitations in fulfilling the religious obligations associated with Hajj. This research contributes to understanding how digital transformation influences religious practices and highlights the tension between technological advancements and traditional rituals.